Effects of weight, height, and reach on the performance of the conventional and grab starts in swimming - Disch, J. G.; Hosler, W. W.; Bloom, J. A. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Therefore, the problem of this study was to examine the effects of weight, height, and reach on the performance of various components of the grab and conventional starts in swimming. The components are: reaction time-time from starting stimulus to first visible movement; movement time-time from first visible movement to toe clearance off the blocks; and flight time-time from toe clearance until entry into the water. The research hypothesis of this study was that weight, height, and reach would be significantly related to these three components of the swim start.